Model Pemberdayaan Perempuan Miskin melalui Pengembangan Kewirausahaan Keluarga Menuju Ekonomi Kreatif di Lampung - Novalita Novalita; Arie Sarjono (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
This research underlines several issues concerning the empowerment of poor women through family-based entrepreneurship towards creative economy. The research was intended to explore the potentials, constraints, opportunities and policies dealing with the empowerment of poor women, and to formulize a model for the empowerment. Data collection consisted of site observation, interview, focus group discussion, and document study. The techniques of analysis employed in this research included interactive analysis and gender analysis by Sara Longwee. opportunities, interventions in the form of family-based entrepreneurship, and welfare.